Influencing factors and optimization paths of teachers’ fulfillment of school bullying governance responsibilities in China - Fuyu Li; Xiaohu Yang; Shifang Meng; Haibo Zhang (PLoS ONE, 2025)
The effective fulfillment of teachers’ responsibilities is crucial to the governance of school bullying. Guided by Grounded Theory and utilizing NVivo11 qualitative analysis software, this paper used 316 texts from 55 cases of school bullying in China to conduct open coding, spindle coding and selective coding, analyzed the behavior of teachers, explored the impetus factors and resistance factors influencing teachers’ fulfillment of their responsibilities, and constructed a “two-factors model”. The reasons why these factors in the model affect school bullying governance responsibility of teachers were analyzed through Street-Level Bureaucracy Theory. On the one hand, teachers are legally obligated to provide fair and equitable educational services to students. The media and the public are important forces in monitoring teachers’ fulfillment of their responsibilities. Additionally, leaders from school and the local government such as police department utilize interdependency and gaming relationships with teachers to promote teachers’ fulfillment of their responsibilities. Furthermore, the formulation of laws and policies is an important basis for supervising teachers’ behavior. These factors collectively promote teachers’ fulfillment of school bullying governance responsibilities. On the other hand, teachers have discretion and are difficult to supervise and hold accountable. The interests of different governance subjects may diverge or conflict. Moreover, the complexity and diversity of school bullying exacerbate governance challenges. Furthermore, systems such as laws and policies often fall short in restraining undesirable behavior. These reasons present obstacles to teachers’ fulfilling their responsibilities of school bullying governance. In order to strengthen the impetus factors for teachers to fulfill their responsibilities and mitigate resistance, China needs to optimize the governance path. This involves improving the relevant systems, enhancing publicity, providing education and training for teachers, strengthening the supervision of the local government, the media and the public on teachers, and improving the overall governance environment for school bullying. These measures will encourage teachers to hold themselves to higher standards and effectively fulfill their responsibilities in the governance process of school bullying.